Pengaruh Model Discovery Learning Berbasis Modul Ajar Terhadap Hasil Belajar Kognitif Siswa Materi Fluida Statis - Rahayu, Rika; Safriana, Safriana; Fatmi, Nuraini; Sakdiah, Halimatus; Widya, Widya (Universitas Garut, 2025)
This study aims to analyze the effect of applying the discovery learning model based on the teaching module on students' cognitive learning outcomes on static fluid material in class XI SMA Negeri 6 Lhokseumawe. This study uses a quantitative approach with a pretest-posttest group method design. The research subjects consisted of XI science class students in the eighth semester, with a total sample of 56 students selected randomly. Data collection was done through interviews and cognitive tests, which consisted of pretests and posttests in the form of multiple-choice questions. Data analysis techniques used include normality tests, homogeneity tests, and hypothesis testing. Class XI IPA 1 was designated as the experimental group that received learning intervention based on the discovery learning model with the teaching module. The results showed that the average cognitive learning achievement of students reached 79 with a standard deviation of 15.63. The module-based discovery learning model is proven to improve students' cognitive learning outcomes in a static fluid material. This is shown through the average posttest score of 79, which meets the good category, as well as the results of hypothesis testing which shows a significance level of 0.000 <0.05, so Ha is accepted. Thus, it can be concluded that the application of this learning model contributes to increasing students' understanding and creativity in learning physics, which is reflected in their optimal cognitive achievement. Keywords: discovery learning, posttest, pretest, static fluid